A Case of Disseminated Carcinomatosis of the Bone Marrow Caused by Recurrence of Sigmoid Colon Cancer After Surgery - Moriwaki, Yoshihiro; Kawakami, Koki (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2025)
A 63-year-old female patient with cancer of the sigmoid colon was referred to our department for surgery. The cancer had invaded the bladder and the left ovary, but there was no distant metastasis. Therefore, we performed resection of the sigmoid colon, a part of the bladder, and the left ovary. Postoperative histopathological examination revealed poorly differentiated and moderately differentiated tubular adenocarcinoma invading the bladder and left ovary, but the surgical margins were negative. Lymph node metastasis was observed, so that we classified the cancer as Stage IIIc and started the patient on adjuvant chemotherapy with CAPOX. Follow-up CT after completion of 8 courses of chemotherapy revealed no evidence of recurrence, although PET-CT showed extensive uptake in the spine and iliac bones. Blood tests revealed Disseminated Intravascular Coagulation Syndrome (DIC), based on which we diagnosed the patient as having disseminated bone marrow carcinomatosis and hospitalized the patient. The DIC progressed rapidly, resulting in subarachnoid hemorrhage and subdural hematoma, making further chemotherapy unfeasible. Thereafter, the condition progressed to brain herniation and the patient died. Reports have shown that prompt initiation of chemotherapy can lead to rapid resolution of DIC and extend patient survival. Therefore, in patients with suspected disseminated bone marrow carcinomatosis, early introduction of chemotherapy as an oncologic emergency is necessary.